Secret war in the Pacific Peter Parsons and Moon River Productions. - Parsons, Peter; Cavett, Morgan; Anderson, John.; Guillermo, Lucky; Leese, Howard; Nevil, Steve; Moon River Productions (Riverside, CA Peter Parsons ; Moon River Productions, 2006)
The story of Commander Charles "Chick" Parsons, the man General Douglas MacArthur called the bravest man he had ever known.
Main feature (50 min.) -- "The making of a secret war" (41 min.)
Summary taken from container.
Written & directed by Peter Parsons and Morgan Cavett ; additional direction, photography, writing and editing by John Anderson, Lucky Guillermo ; original music composed by Howard Leese.
Narrated by Steve Nevil and John Anderson.
Keywords: Parson, Charles -- 1902-1988.; MacArthr, Douglas -- 188-1964.; World War, 1939-1945 -- ampaigns -- Philippines; World War, 1939-1945 -- ampaigns -- Pacific; World War, 1939-1945 -- ampaigns -- Naval operations, American; Documentary films; Nonfiction films